2017
DOI: 10.4097/kjae.2017.70.5.535
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone alone versus in combination with intra-operative super-hydration for postoperative nausea and vomiting prophylaxis in female patients undergoing laparoscopic cholecystectomy: a randomized clinical trial

Abstract: BackgroundDexamethasone has a prophylactic effect on postoperative nausea and vomiting (PONV) and perioperative hydration is believed to play a role in PONV prophylaxis. This study was performed to examine the combined effects of pre-induction dexamethasone plus super-hydration on PONV and pain following laparoscopic cholecystectomy (LC).MethodsA total of 100 female patients undergoing LC were enrolled and randomized equally into two groups. Group DF received 5 mg dexamethasone (pre-induction) plus 30 ml/kg Ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 29 publications
1
18
0
2
Order By: Relevance
“…Pemberian CHO praoperasi dapat menurunkan resistensi insulin dikarenakan masih terdapat glukosa di dalam sirkulasi selama masa operasi sehingga emetik sehingga terjadi PONV. 1,9,10,13 Pada penelitian ini didapatkan efek CHO dalam menurunkan kejadian PONV signifikan dalam 0-120 menit dan tidak signifikan pada 2-24 jam pascaoperasi. Hal ini tidak sesuai dengan penelitian sebelumnya yang dilakukan pada 40 pasien yang menjalani operasi laparoskopik kolesistektomi yang menunjukkan pemberian CHO mengurangi PONV hingga 24 jam pascaoperasi.…”
Section: Subjek Dan Metodeunclassified
See 1 more Smart Citation
“…Pemberian CHO praoperasi dapat menurunkan resistensi insulin dikarenakan masih terdapat glukosa di dalam sirkulasi selama masa operasi sehingga emetik sehingga terjadi PONV. 1,9,10,13 Pada penelitian ini didapatkan efek CHO dalam menurunkan kejadian PONV signifikan dalam 0-120 menit dan tidak signifikan pada 2-24 jam pascaoperasi. Hal ini tidak sesuai dengan penelitian sebelumnya yang dilakukan pada 40 pasien yang menjalani operasi laparoskopik kolesistektomi yang menunjukkan pemberian CHO mengurangi PONV hingga 24 jam pascaoperasi.…”
Section: Subjek Dan Metodeunclassified
“…Jika iskemia ini tidak dikoreksi akan menyebabkan pelepasan serotonin berlebihan yang dapat mencetuskan PONV. 9,10 Beberapa penelitian sudah dilaksanakan sebelumnya, penelitian yang dilakukan di India pada pasien yang menjalani prosedur laparoskopi menyatakan penurunan kejadian PONV yang signifikan pada pasien yang diberikan terapi CHO praoperasi dibanding dengan pasien yang tidak diberikan CHO sebesar 38-60%. 1 Tujuan penelitian ini adalah mengetahui pengaruh pemberian minuman karbohidrat praoperasi terhadap kejadian mual dan muntah pascamastektomi.…”
unclassified
“…In a minority of studies, comparator groups were administered an i.v. supplemental crystalloid bolus comparable to this volume[25,29,32,35,37,40,41,45,53,54,58].Figure 2shows the risk of bias for each study. This was generally low to moderate across all included studies, but eight studies were at high risk of bias[20,21,42,43,47,48,56,59].…”
mentioning
confidence: 99%
“…One study (30 participants) used a dextrose-containing solution in the intervention group[52], and a sensitivity analysis found that inclusion of this study did not substantially affect the risk ratio or the statistical heterogeneity. Additional planned sensitivity analyses of studies at low risk of bias[23,24,29,36,41,46,49], and of studies administering comparator groups at least 10 ml.kg -1 of supplemental i.v.crystalloid[29,32,41,45,54] also did not substantially affect the risk ratio.…”
mentioning
confidence: 99%
“…We read with great interest the article of Ismail et al [ 1 ] in a recent issue of the Journal. The authors performed a randomized controlled trial in 100 female patients who underwent laparoscopic cholecystectomy.…”
mentioning
confidence: 99%